INVENTARISASI PARASITOID ULAT API Setora nitens WLK. (Lepidoptera: Limacodidae) ASAL PERKEBUNAN KELAPA SAWIT DI KECAMATAN PERHENTIAN RAJA KABUPATEN KAMPAR PROVINSI RIAU - Boris Satriyo Situmorang; Rusli Rustam; Desita Salbiah (UIR Press, 2016)
Setora nitens Wlk. is a palm oil leaf-eating larvae that dominantly existed in Riau Province. Setora nitens could causing a significant losses if there is no control for their population growing. Parasitoids are included as the biological control agent which can be used as a natural enemies to sppress the population density of Setora nitens in palm oil plantation. This research aims to inventorizing the parasitoids, calculating both rates of parasitism and sex ratio of parasitoids that could parasitizing Setora nitens on a palm oil plantation in Subdistrict of Perhentian Raja, District of Kampar, Province of Riau. This research was using a purposive sampling as the survey method to determine the research’s scope. The research’s scope criteria is a palm oil plantation that were attacked by Setora nitens and has a possibilities as the parasitoids habitat. The research location was an expanse of palm oil plantations which covering 6 Ha and diagonally were set 5 sample points, which each point was randomly taken 5 plants as a sample, so there were 25 plants as the total sample. The results of rearing the Setora nitens larvae in Plant Pest Laboratory, Faculty of Agriculture, University of Riau has discovered one kind of parasitoid known as endoparasitoid, derived from the Ordo Hymenoptera, Subordo Apocrita and Family Braconidae with a total number of individuals are 49 tails. The percentage rate of parasitism that had occured reached 33.3%, while the parasitoid sex ratio range between males and females were between 1.4: 1 and 2.5: 1.